Tax Allowance – Mengapa Tidak Berjalan? - Basalamah, Anies Said (Badan kebijakan Fiskal, 2018)
Since September 2015 President Joko Widodo has been launching The Economic Policy Packages that up to July 2017 have been in fifteen volumes. Although many argue that these Economic Policy Packages are failed, this research shows that one of those Economic Policy Packages is not failed although it cannot be considered successful as well since up to July 2017, there were only 37 Tax Payers got the tax allowance facilities. This research also shows the many potentials for the Volume II Economic Policy Package to be failed, including Government Regulation Number 18 of 2015 as well as Number 9 of 2016 in addition to the regulations following those two Government Regulations that are inconsistency, uncoordinated, and having different procedures for different ministerial sectors regarding the industries of the Tax Payers. In this research the authors recommend that Government Regulation Number 18 of 2015 and Number 19 of 2016 are changed and replaced by single Government Regulation that is more operational, thrive among those of ministerial sectors, and giving more assurance in applying the laws and regulations.Sejak tahun 2015 Pemerintahan Presiden Joko Widodo meluncurkan Paket Kebijakan Ekonomi dalam 15 jilid. Meskipun beberapa pihak menilai kebijakan ini gagal, penelitian ini menunjukkan salah satunya tidaklah dapat disebut gagal meskipun tidak dapat juga dikatakan berhasil karena hingga 25 Juli 2017 hanya ada 37 Wajib Pajak yang berhasil memperoleh fasilitas tax allowance. Penelitian ini menunjukkan potensi kegagalan tersebut berasal dari Peraturan Pemerintah itu sendiri beserta peraturan-peraturan pelaksanaannya yang tidak konsisten, tidak terkoordinasikan dengan baik dan menggunakan mekanisme, tata cara atau prosedur yang berbeda-beda antar kementerian sektor yang membidangi industri tempat Wajib Pajak menjalankan usaha mereka. Dalam penelitian ini penulis merekomendasikan agar Peraturan Pemerintah tersebut dicabut dan diganti dengan yang lebih operasional, tidak bertabrakan antar kementerian sektor, dan lebih memberikan kepastian hukum.